Delegation of Authority as a Technology of Effective Pedagogical Management - Shvardak, Marianna; Halus, Oleksandr (Pedagogical Discourse, 2021)
The article outlines the preconditions for the emergence of delegation of authority. The categorical apparatus of the research is determined. The essence of key definitions (delegation of powers, powers, responsibilities, technology of delegation of powers) is specified. Types of powers (linear and branched) are defined. The principles (single-headedness, limitation of the norm of controllability, conformity of rights to obligations, assigned responsibility, interim reporting) and rules of delegation of powers are generalized. Typical barriers to delegation are identified. The specifics of the application of the technology of delegation in educational institutions are revealed, which consists in the fact that its competent implementation in managerial activity enables the educational manager to deal with the tasks of the highest level; identify potential opportunities for teachers, reveal their abilities, professional qualifications; help create synergies, form a team of like-minded people; create additional motivation, involvement of each employee in the common cause; to provide the best result, after all the certain work of the expert of the corresponding direction is capable to carry out more professionally, than the head. An algorithm for the application of delegation technology has been developed. The advantages and disadvantages of delegation of powers in the conditions of educational institutions are revealed. Recommendations to the head of a modern institution of general secondary education for competent and effective delegation of powers are formed.